Chapter Il 'canto dell'acqua': Leonardo nel progetto dei nuovi Navigli milanesi - PRUSICKI, MARCO STANISLAO (Territori, 2023)
After a long process, the reopening of Milanese canals has become one of the fundamental actions of the Town Plan approved in 2019. A strategic project that plans to reactivate the covered section of the Naviglio Martesana and the Cerchia Interna, reuniting Adda and Ticino rivers, and give new life to the great Renaissance project that Leonardo himself had worked on. In its methodological approach and in the specific outcome achieved, we can recognize elements of continuity with Leonardo's thinking and contribute to a territorialist reflection on its current relevance.